Genetic analyses of advanced breeding lines of rice for yield-attributing traits and salinity stress tolerance - Khatun, Sheikh Mahfuja; Naim, Jannatul; Das, Biswajit; Mim, Mumtarin Haque; Akter, Sadia; Yasmin, Sabina; Hossain, Mohammad Anwar (Journal of Phytology, 2024)
The development of advanced rice breeding lines and their evaluation for yield-attributes and salinity stress tolerance offers a significant opportunity to identify high-yielding salt-tolerant genotypes exhibiting desired traits. The present study aimed to examine the morpho-genetic variability of thirty-six advanced breeding lines of rice, with a focus on features that contribute to yield and salinity stress tolerance. Three replications of a randomized complete block design were used in the first experiment. Significant variability was observed among the lines for the studied quantitative traits. Based on yield attributing traits, the advanced breeding lines viz., Line 10, Line 21, Line 22, Line 23, Line 24 and Line 25 showed better performances in terms of earliness and yield. In yield-related variables such as the number of effective tillers per plant, plant height, and grain yield per plant exhibited high heritability coupled with high genetic advance as percentage of mean. The results of PCA biplot showed that the PC1 and PC2 accounted for the greatest variability of advanced Line 10, Line 11, Line 18, Line 21, Line 22, Line 23, Line 24, Line 25, Nerica 10, Begunipata, and Binadhan-14 with significant influence of the studied traits. Cluster analysis reflected that the high-yielding genotypes were placed in cluster II and VI. Highest genetic distance was observed among the genotypes of cluster III and cluster VI. In the second experiment, four advanced breeding lines along with salt tolerant and susceptible checks were assessed for salinity tolerance at the reproductive stage. The plants were cultivated in a large plastic-tub filled with field soil. During the late booting stage, saline (EC=10 dS/m) irrigation water was applied to the plants and continued for three weeks. While Lines 10 and 12 demonstrated a reduced decline, salt stress caused a significant loss in yield and yield-attributing characteristics in all genotypes. Line 10 and Line 12 which showed a reasonable degree of salt tolerance as well as early maturity were placed in the respective quadrant of the biplot. Stress tolerance indices also reflecting the better salt tolerance phenomena of the advanced Line 10 and Line 12. Considering all of the traits, Line 10 and Line12 could be selected as desired advanced rice lines for the development of early, high-yielding and salt tolerant rice varieties.